Comparison of Polyvinyl Acetate Sponge and Medicated Ribbon Gauge Nasal Pack following Nasal Surgery - Maharjan, Shova; Jha, AK; Joshi, RR; Rijal, AS; Shrestha, KK; Dhungana, A (Nepal Medical College Journal, 2019)
Nasal occlusive dressings are routine after nasal surgeries to arrest hemorrhage, to prevent septal hematoma, and to prevent postoperative adhesions. However, patients describe nasal packing and its removal as their worst experience. Various types of nasal packs are available. Medicated ribbon gauge is the traditional form of nasal pack which consists of an open-mesh cotton as a carrier whereas “Polyvinyl Acetate’ sponge is a compressed dehydrated material, an improvised one which increases in size and compresses blood vessels when rehydrated with normal saline. As Polyvinyl acetate sponge is smooth and spongy, it causes less pain and abrasion while in-situ and removal. This was a prospective comparative study done in tertiary hospital of Nepal. Patients were subjected to either polyvinyl acetate sponge or ribbon gauge nasal pack following nasal surgery. Comparisons were made in terms of pain score, maintenance of hemostasis and wound healing. There were 154 patients in the study with 104 males and 50 females. The pain score when nasal pack was in-situ was similar in both groups whereas it was lesser in the polyvinyl acetate group on its removal. However, bleeding and adhesion were found to be similar. Crust formation was less in polyvinyl acetate group. Six synaechia were noted in ribbon gauge group only. Pain was significantly less during removal of polyvinyl acetate pack.